Case Report of Lower Respiratory Tract Infection Improved Only on Empirical Antifungal Agent - Bashyal, R.; Sunari, R.; Poudel, R. (Devdaha Medical Journal, 2024)
Introduction: Fungal pneumonia is an infection of the lungs brought on by natural or opportunistic fungi. It is mostly airborne and commonly affects those who are susceptible to infection or are immunocompromised.Clinical case: A patient presented with a clinical symptom of pneumonia, who, after evaluation was suspected with fungal pneumonia and treated empirically. The patient improved and recovered.Discussion: The incidence of invasive fungal infections is rising, and many patients may present with pneumonia-like signs and symptoms that resemble bacterial infections. However, fungal pulmonary infections should also be considered in the differential diagnosis.Conclusion: Fungal pulmonary infections are prevalent. Hence, recognizing key fungal pathogens and their features is crucial for accurate diagnosis and treatment.